Bond investigations of prestressed, near-surface-mounted, ribbed memory-steel bars with full bond length. (November 2020) - Schranz, Bernhard; Czaderski, Christoph; Vogel, Thomas; Shahverdi, Moslem
Abstract: The effectiveness of iron-based shape memory alloy (Fe-SMA, 'memory-steel') reinforcements has been proven in several studies and site applications. Due to the novelty of ribbed memory-steel reinforcement bars, limited research has been performed on their application in structural engineering, however. In this study, the bond behaviour of memory-steel bars in a near-surface-mounted configuration designed for prestressed strengthening of concrete structures was investigated. Memory-steel bars were installed on concrete blocks and activated by resistive heating before being subjected to pull-out load. The effects of heating and hence prestressing, bar ductility, bond length and rigidity of the fixation were studied based on obtained prestress, crack development, slip and bar strain. During activation of the bars, a longitudinal splitting crack with insignificant crack width occured. Two failure modes were observed during subsequent external loading, including tensile rupture of the bar when less ductile material was used, or bond failure when material with higher ductility was under investigation. Initial prestressing did not result in a reduced bond capacity. Based on the differential equation of bond behaviour, an analytical calculation procedure was developed that enables prediction of bond shear stress, slip, bar strain, pull-out load, as well as the use of a non-linear material behaviour. Graphical abstract: Unlabelled Image Highlights: Heating of near-surface-mounted ribbed Fe-SMA bars bonded on one bar end led to successful prestress in the free bar length. A longitudinal splitting crack with insignificant crack width was observed along the embedded length during heating. Pull-out loading revealed that the heating and hence prestressing did not have a detrimental effect on the bond capacity. Two materials with different ductility led to either rupture of the bar or bond failure. Predicted distributed bond shear stress, slip, strain showed agreement with the data using a nonlinear material behaviour.